Comparison of modified anterior and traditional posterior accesses for ultrasound-guided superior laryngeal nerve block in awake endotracheal intubation: study protocol for a randomised non-inferiority clinical trial - Guo Chen; Tao Zhu; Yusi Hua; Qiyuan Huang (BMJ Open)
Introduction Awake tracheal intubation (ATI) involves placing a tracheal tube in an awake, spontaneously breathing patient. Superior laryngeal nerve block (SLNB) can effectively abolish the glottic closure reflex, and blunt the sensation of the structures above the cords. A method that consists of SLNB along with translaryngeal injection (TLI) can provide satisfactory anaesthesia and intubating conditions. We present a novel modified access of SLNB, ultrasound (US)-guided anterior SLNB, to aid awake videolaryngoscopes-assisted endotracheal intubation in adult elective surgery patients, and we compare the effectiveness and safety to traditional US-guided posterior SLNB.Methods and analysis A total of 100 adult elective surgery patients requiring general endotracheal anaesthesia will be randomly assigned to the modified group (modified US-guided anterior SLNB) or the traditional group (traditional US-guided posterior SLNB). After SLNB, all participants will be performed with TLI. The primary outcome is the proportion of acceptable intubation conditions based on intubation scores. Secondary outcomes include: (a) the first-attempt intubation success rate, (b) haemodynamic changes during ATI, (c) time taken for airway anaesthesia and intubation, (d) recall of intubation, (e) participant perception of comfort during intubation, (f) perioperative complication rate. This report describes the study design of this randomised controlled trial.Ethics and dissemination The study protocol has been approved by an ethical committee of the West China Hospital (Sichuan University), and registered at the Chinese Clinical Trials Register (www.chictr.org.cn). Results will be published in a peer-reviewed journal.Trial registration number ChiCTR2200058086.